2010
DOI: 10.4314/gmj.v41i4.55284
|View full text |Cite
|
Sign up to set email alerts
|

Population based reference intervals for common blood haematological and biochemical parameters in the Akuapem north district

Abstract: SUMMARYObjectives: To estimate the reference intervals for commonly used blood haematology and biochemical parameters in an adult (18-55yrs) population of residents of Mampong Akuapem. Design: This was a population based cross sectional study of a randomly selected sample of the adult population of Mampong. The sample was selected from an updated census list of the Mampong area. Conclusion:In comparison to reference values that are commonly used in Ghana, the haemoglobulin levels from this study were lower, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
42
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 8 publications
13
42
2
1
Order By: Relevance
“…The lower RI indicates preponderance of vegetarian and young individuals participating in the study. Despite different methodology adopted and different racial population RI observed for these biochemical parameters are almost similar to studies conducted in different countries [15][16][17][18][19].…”
Section: Resultssupporting
confidence: 75%
“…The lower RI indicates preponderance of vegetarian and young individuals participating in the study. Despite different methodology adopted and different racial population RI observed for these biochemical parameters are almost similar to studies conducted in different countries [15][16][17][18][19].…”
Section: Resultssupporting
confidence: 75%
“…Laboratory reference values for populations from western countries are widely published in scientific literature [2], textbooks and on the worldwide web. However, there is a general lack of published data regarding laboratory parameters for populations living in tropical sub-Saharan Africa [3] and the few studies that have been undertaken have indicated differences in reference values of African populations compared to those derived from western populations [3][4][5][6]. These differences suggest the need for the development of locally derived reference values.…”
Section: Introductionmentioning
confidence: 99%
“…These differences suggest the need for the development of locally derived reference values. Reference values are used to aid in interpreting results of laboratory measurements, clinical trials screening and as the basis of safety monitoring for trial participants [3,5,6]. These reference values are used to assess health in humans and are based on the effective performance of the major body organs such as the liver, pancreas, heart and kidney.…”
Section: Introductionmentioning
confidence: 99%
“…(MCH) by gender have been observed in several African studies, with adult males having higher values than adult females in East Africa [9,16,20,31,39,40], Southern Africa [20,36], West Africa [41] and Central Africa [42]. These gender differences in RBC parameters as illustrated in our findings (Table 2), are consistent with previously established evidence that males have higher values than females for these parameters and is partly attributed to the influence of the androgen hormone on erythropoiesis [43,44] and to menstrual blood loss in women [16,25,39,42,45].…”
Section: Laboratory Reference Intervals In Africa 309mentioning
confidence: 99%